Pertanggungjawaban Hukum Terhadap Kejahatan Perang di Palestina Oleh Israel dalam Perspektif Hukum Pidana Internasional - Azhar, Bintang; Todi, Yusuf Afrenoldi; Er, Vickri Hafis Fadillah; Hosnah, Asmak UI (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
The armed conflict between Israel and Palestine has resulted in numerous violations of international humanitarian law, including acts that may constitute war crimes. This study aims to analyze the forms of war crimes committed by Israel in Palestinian territories and to examine the mechanisms of legal accountability applicable under international criminal law. The research employs a normative juridical method using statutory and case approaches, focusing on international legal instruments such as the 1998 Rome Statute, the 1949 Geneva Conventions, and relevant United Nations Security Council resolutions. The findings indicate that Israel’s military actions—such as attacks on civilians, destruction of humanitarian facilities, and disproportionate use of force—fulfill the elements of war crimes as stipulated in Article 8 of the Rome Statute. However, the enforcement of legal accountability against Israel faces significant political and juridical obstacles, primarily due to Israel’s non-membership in the Rome Statute and the influence of veto powers within the UN Security Council. Therefore, the pursuit of justice for war crimes in Palestine requires stronger international support and reforms within the International Criminal Court system to ensure the effective realization of universal justice principles.